ChemInform Abstract: Nontypical Luminescence Properties and Structural Relation of Ba3P5N10X:Eu2+ (X: Cl, I): Nitridophosphate Halides with Zeolite‐Like Structure. Issue 48 (December 2015) - Marchuk, Alexey; Wendl, Sebastian; Imamovic, Nedzada; Tambornino, Frank; Wiechert, Detlef; Schmidt, Peter J.; Schnick, Wolfgang
Abstract: Ba3 P5 N10 X (X: Cl, I) are prepared by hot press‐sintering of stoichiometric mixtures of Ba(N3 )2, P3 N5, and BaX2 (h‐BN crucible in multianvil press, 1—5 GPa, 1000 °C, 2 h).